DEVELOPMENT OF INTERACTIVE LEARNING MEDIA LECTORA INSPIRE ON BASIC BANKING SUBJECT TO IMPROVE STUDENT’S LEARNING INTEREST - Pratiwi Apriniya; Mimin Nur Aisyah (Jurnal Pendidikan Akuntansi Indonesia, 2019)
This research aimed to develop interactive learning media with Lectora Inspire for the students of grade X AKL SMK Negeri 1 Tempel on Basic Banking subjects with the competence of saving. The research used the Research Development with ADDIE (analysis, design, development, implementation, evaluation) model. The media was assessed by material expert, media expert, and teacher. The results show that the feasibility of interactive learning media by material expert in strongly feasible category (average score of 4, 26), by media experts in strongly feasible category (average score of 4, 36), by teacher in strongly feasible (average score of 4, 33), and by students in feasible category (average score of 4, 07). The interactive learning media developed is strongly feasible to be used as learning media for students. The student’s learning interest before and after the use of interactive learning media has increased by 8% from 64% to 72%. Paired sample t-test obtained tcount  -5.213 with sig 0.000 showed significant learning interest’s improvement. Therefore, it can be concluded that interactive learning media is able to improve student’s learning interest. Keywords: Interactive Learning Media, Lectora Inspire, Student’s Learning Interest.